Effects of Linagliptin and Pioglitazone on Fracture Healing in an Experimental Type 2 Diabetes Rat Model - Mraja, Hamisi M.; Caglar, Sever; Uslu, Muhammed; Yilmaz, Bilal; Dasci, Mustafa Fatih; Sarac, Elif Yaprak; Demirkol, Metehan (CUREUS INC, 2022)
Aim: Our study aimed to examine the effects of Linagliptin, Pioglitazone, and their combination on fracture healing in a diabetes rat femur fracture model. Material and methods: Type 2 diabetes mellitus (T2DM) induced rats were randomly divided into four groups: non-treated diabetes group (TD), Pioglitazone group (P), Linagliptin group (L), and Pioglitazone and Linagliptin group (PL). Daily oral dosage of pioglitazone (10 mg/kg/day), linagliptin (10 mg/kg/day), and their combination were administered. Femur fractures were stabilized intramedullary. At weeks 2 and 6, rats were sacrificed for evaluation radiologically, biomechanically, histopathologically, histomorphometrically, and immunohistochemically. Results: Flexural strength of the L and PL groups were significantly higher compared to the P group. The highest healing score was in the L group and lowest in the P group, while the highest inflammation score was in the P group and lowest in the L group. A cluster of differentiation (CD) CD 34 reactivity was highest in the L group and lowest in the PL group. Conclusion: Linagliptin treatment significantly increased histological healing scores, callus volume, biomechanical strength, and vascularity, however, minimized the inflammatory process, which was increased by pioglitazone. The combination of linagliptin and pioglitazone restored BMD and increased biomechanical strength. Linagliptin monotherapy is rarely indicated; hence, T2DM patients with a high risk of bone fractures can be considered for combined therapy of pioglitazone and linagliptin.
Keywords: type 2 diabetes; streptozotocin; pioglitazone; linagliptin; bone healing; DIPEPTIDYL PEPTIDASE-4 INHIBITORS; GROWTH-FACTOR VEGF; COMBINATION THERAPY; BONE-RESORPTION; QUALITY; THIAZOLIDINEDIONES; VILDAGLIPTIN; MELLITUS; EFFICACY; General & Internal Medicine